The reciprocal impact of electoral turnout on protest participation in developing countries: evidence from Iran's 2018 uprising. Issue 4 (19th May 2021) - Raisi, Alireza
ABSTRACT: Despite a rich body of scholarship in social movements and electoral studies, the interaction between electoral turnout and protest participation has been generally overlooked. This article aims to bridge this gap by examining the impact of electoral participation on the likelihood of protest activities in developing countries. Drawing from a statistical analysis of a unique set of data from Iran's 2017 election and the following uprising, the article argues that a higher electoral turnout reduces the likelihood of protest incidence at the district level. The analysis further indicates that such turnout mediates between economic grievances and protest participation.